2019
DOI: 10.18632/aging.102245
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of antihyperglycemic medication exposure and survival in patients with gastric cancer

Abstract: Objective: We aimed to estimate survival in gastric cancer patients with type 2 diabetes mellitus (T2DM) using different antihyperglycemic medication.Methods: Patients with gastric cancer and diabetes between 2003-2013 were identified form The Lithuanian Cancer Registry and The National Health Insurance Fund database. Cohort members were classified into five groups: four groups of T2DM patients according to treatment: metformin users; metformin and other medication users; sulphonylurea users; insulin and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…These results were agreement with results obtained by Alehagen et al (12) who found that, there were significant differences between T2DM and IFG according to CoQ10 (P < 0.001). Dulskas et al, (13) found that, there were no significant difference between T2DM and IFG according to age (P 0.89), BMI (P 0.74), this result was agreement with results in this study. A study of (14) found that, there were significant differences IGFBP in patients with T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…These results were agreement with results obtained by Alehagen et al (12) who found that, there were significant differences between T2DM and IFG according to CoQ10 (P < 0.001). Dulskas et al, (13) found that, there were no significant difference between T2DM and IFG according to age (P 0.89), BMI (P 0.74), this result was agreement with results in this study. A study of (14) found that, there were significant differences IGFBP in patients with T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the GII combination treatment, although the GH-cancer relationship has been a subject of discussion (38), previous in vitro and in vivo studies have demonstrated that it does not exhibit pro-tumor effects (39)(40)(41). Furthermore, although insulin promotes malignant cell proliferation and invasiveness in vitro (42,43), however, contradictory effects have been reported regarding cancer survival and risk in patients (44)(45)(46). According to these studies, in the present model, GII treatment did not show pro-tumor effects, although GII-treated cells expressed GH and insulin receptors, as well as cyclooxygenase (data not shown).…”
Section: Discussionmentioning
confidence: 50%
“…Regarding the GII combination, despite that GH raises concerns about its pro-tumoral effects 30 , in vitro and in vivo studies demonstrate that it does not stimulate cancer progression [31][32][33] . Insulin, on the other hand, does increase malignant cell proliferation and invasiveness 34,35 , but these effects are at least inconsistent regarding cancer risk and survival in patients [36][37][38] . According with these studies, in our model neither GH, insulin, nor indomethacin modified cancer growth in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%